Plasmonic nanojet: an experimental demonstration; Optics Letters; Vol. 45, iss. 12 - Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich; Glinsky I. A. Igor Andreevich; Khabibullin R. A. Rustam Anvarovich; Malureanu R. Radu; Lavrinenko A. V. Andrey Vladimirovich; Yakubovsky D. I. Dmitry Igorevich; Arsenin A. V. Aleksey Vladimirovich; Volkov V. S. Valentin Sergeevich; Ponomarev D. S. (2020, 2020)
Title screen